Stable mode-locked fiber laser using 49 cm long bismuth oxide based erbium doped fiber and slow saturable absorber - Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Akbari, Reza; Ahmad, Harith (IOP Publishing, 2011)
A stable mode-locked fiber laser employing a 49 cm long bismuth oxide based erbium doped fiber (Bi-EDF) by using a slow saturable absorber is demonstrated. Near transform limited short pulses with a repetition rate of 8.27 MHz are obtained at a wavelength of 1560 nm with a maximum spectral width of 15 nm. Results indicate that pulse characteristics are strongly dependent on pump power rather than spectral width. Moreover the Time-Bandwidth products (TBWP), pulse duration, the energy fluctuation and timing jitter decrease with increasing pump power. The pulse width is continuously varied from 1.2 ps to less than 300 fs. It produces stable mode locking with a maximum spectral width of 15 nm, minimum timing jitter of 4 ps and energy fluctuations of 2.5%. The pulse train was amplified using a two-stage amplifier up to 447 mW average power corresponding to peak powers of 177.3 kW.